2008
DOI: 10.1073/pnas.0807121105
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tag density required for digital transcriptome analysis: Application to an androgen-sensitive prostate cancer model

Abstract: High-throughput sequencing has rapidly gained popularity for transcriptome analysis in mammalian cells because of its ability to generate digital and quantitative information on annotated genes and to detect transcripts and mRNA isoforms. Here, we described a double-random priming method for deep sequencing to profile double poly(A)-selected RNA from LNCaP cells before and after androgen stimulation. From Ϸ20 million sequence tags, we uncovered 71% of annotated genes and identified hormone-regulated gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 30 publications
1
88
0
Order By: Relevance
“…Specifically, their study used a DNA microarray and RNA sequencing platform, and they identified the same gene signature for which the resulting drug (cotinine) suppressed androgen-driven cell proliferation [61]. Furthermore, they experimentally validated cotinine, which inhibits proliferation in LNCaP cells [60].…”
Section: Discovering Novel Phenotypic Relationsmentioning
confidence: 99%
“…Specifically, their study used a DNA microarray and RNA sequencing platform, and they identified the same gene signature for which the resulting drug (cotinine) suppressed androgen-driven cell proliferation [61]. Furthermore, they experimentally validated cotinine, which inhibits proliferation in LNCaP cells [60].…”
Section: Discovering Novel Phenotypic Relationsmentioning
confidence: 99%
“…In contrast, RNA-Seq provides a relatively unbiased and direct digital readout of cDNA sequence generated from an RNA sample. Several studies have demonstrated that RNA-Seq provides an extremely reproducible and quantitative readout of transcript abundance (e.g., Li et al 2008;Marioni et al 2008;Pan et al 2008;Wang et al 2008). Because RNA-Seq is performed using tagged libraries of short cDNAs, prepared from fragmented or unfragmented RNA, it does not require prior knowledge of the sequences to be profiled.…”
mentioning
confidence: 99%
“…Finally, the fragments are reverse transcribed using primers complementary to the adapters. Several elaborations of the RNA fragmentation approach have been developed (6)(7)(8) to facilitate strand-specifi c sequencing.…”
Section: Rna Isolation and Ribo-depletionmentioning
confidence: 99%